Znaczenie badań preferencji konsumentów dla programowania produkcji żywności ekologicznej - Łaguna, Mirosław; Żuchowski, Ireneusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
This research was aimed at identification of the le vel of consumers' knowledge about ecological food products and at examination of consumer preferences. To understand consumer behaviour, study traced a sample of 200 customers of shops providing with ecological food commodities. The research outcomes show that consumers positively evaluate market offer and are willing to pay higher prices for ecological products.